Strategi Penetapan Harga Jangka Panjang dan Adaptasi Usaha Katering Mama Dian Kitchen dalam Merespons Dinamika Pasar - Purwanti Purwanti; Riska Yunia Andiani; M. Ilham Noer Arif (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
Pricing plays an important role in maintaining the competitiveness and sustainability of a catering business. This research explores Mama Dian Kitchen's long-term pricing strategy and its adaptation to market changes. Using a qualitative case study method through observation, interviews and documentation, the study found that a combination of cost-based and market-response approaches helped increase customer loyalty and maintain profitability. Flexibility in adjusting prices to consumer conditions is a key factor in business sustainability. The findings are relevant to the development of MSME business strategies in the catering sector, especially in the face of market dynamics and changes in consumer behavior